GRP-027 Assessment of Blood Pressure Control and Antihypertensive Medication Adherence in a Portuguese Hypertensive Population. (12th March 2013) - Morgado, M; Silva, J; Almeida, A
Abstract : Background: Hypertension is one of the major causes of worldwide morbidity and mortality. Despite the wide variety and availability of powerful antihypertensive agents, the blood pressure (BP) of fewer than a third of adult hypertensive patients is under control. Non-adherence to medicines is one of the major causes of treatment failure. Purpose: To evaluate BP control and antihypertensive medicines adherence in a Portuguese hypertensive population. Materials and Methods: A cross-sectional observational study was conducted in adult (aged 18 or over) hypertensive patients attending the hypertension/dyslipidaemia clinic for at least 6 months at the university teaching hospital of Cova da Beira Hospital Centre, Covilhã, Portugal, from March to August 2012. Patients were asked to participate in a structured interview which included socio-demographic characteristics, antihypertensive medicines adherence and target BP values. Medicines adherence was measured using a validated five-item adherence scale, [1] derived from the four-item scale developed by Morisky et al, [2] Detailed clinical information was obtained from medical records. Results: A total of 94 patients met the inclusion criteria and completed the structured interview. Of these, the BP of 47% was under control according to the European Society of Hypertension. Antihypertensive medicines adherence was 40%. Patients with controlled BP had a significantly higher rate of medicines adherence than patients with uncontrolled BP (52% vs. 30%, P = 0.028). Likewise, it was observed that patients whose BP was controlled were significantly more aware of their target BP figures (75% vs. 46%, P = 0.034). Conclusions: Many hypertensive patients prescribed antihypertensive treatment fail to achieve BP control in clinical practise. Poor medicines adherence and poor patient knowledge of target BP values should be considered as possible underlying causes of inadequately controlled BP and must be addressed in any intervention aimed to improve BP control. References: Shea S, Misra D, Ehrlich MH, Field L, Francis CK. Correlates of nonadherence to hypertension measurement in an inner-city population. Am J Public Health 1992;82(12):1607–12. Morisky DE, Green LW, Levine DM. Concurrent and predictive validity of a self-report measure of medication adherence. Med Care 1986;24(1):67–74. No conflict of interest.